2008
DOI: 10.1021/pr700840y
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Based on Peptide Fractionation by SDS-Free PAGE

Abstract: Here we demonstrate the usefulness of peptide fractionation by SDS-free polyacrylamide gel electrophoresis and its applicability to proteomics studies. In the absence of SDS, the driving force for the electrophoretic migration toward the anode is supplied by negatively charged acidic amino acid residues and other residues as phosphate, sulfate and sialic acid, while the resulting mobility depends on both the charge and the molecular mass of the peptides. A straightforward method was achieved for SDS-PAGE of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 32 publications
(58 reference statements)
2
35
0
Order By: Relevance
“…In model protein mixtures as a, b, and k-casein as well as egg white, which contain very acidic tryptic peptides including phosphopeptides, several signals were identified in the bands next to bromophenol blue front (Supporting Information I). In agreement with the results at basic pH [18], very acidic peptides and phosphopeptides were detected in the slice containing the fastest migrating species. Interestingly, using the new discontinuous buffer system, fewer nonphosphorylated peptides were detected in this fraction for both samples (caseins and egg white mixture) and the signalto-noise ratio in the spectrum was also improved.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…In model protein mixtures as a, b, and k-casein as well as egg white, which contain very acidic tryptic peptides including phosphopeptides, several signals were identified in the bands next to bromophenol blue front (Supporting Information I). In agreement with the results at basic pH [18], very acidic peptides and phosphopeptides were detected in the slice containing the fastest migrating species. Interestingly, using the new discontinuous buffer system, fewer nonphosphorylated peptides were detected in this fraction for both samples (caseins and egg white mixture) and the signalto-noise ratio in the spectrum was also improved.…”
supporting
confidence: 90%
“…Recently, we reported the use of SDS-free PAGE for peptide fractionation and its usefulness for proteomic studies [18] in combination with a first dimension for protein separation via SDS-PAGE. Peptides fractionated by SDS-free PAGE on the Ornstein gel system had theoretical isoelectric points ranging between 3.0 and 7.3 [18], which suggested that manipulating the pH of the buffer should allow fractionating a different subset of peptides. In the present work, we evaluated the effect of pH on the migration of peptides and developed a discontinuous buffer system to select and simultaneously fractionate peptides with pI lower than 5.5.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The field has seen great development in the last years due to advances in mass spectrometry (MS) instrumentation, the development of new analytical methods (3)(4)(5), and novel computational approaches (2,6). Bottom-up proteomics is currently the standard analytical method to identify and quantify proteins based on the presence of peptides obtained by digestion of the protein mix during sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…The existing comparison has been meager, using limited data [17], or peptides instead of proteins [18,19] or inaccurately reports [17,20]. In other words the pI is obtained incidentally by isoelectric focusing assays, free flow electrophoresis, capillary electrophoresis and gel electrophoresis [21][22][23].…”
Section: Introductionmentioning
confidence: 99%